2018
DOI: 10.1111/cod.12981
|View full text |Cite
|
Sign up to set email alerts
|

Specific barrier response profiles after experimentally induced skin irritation in vivo

Abstract: BackgroundRecently, natural moisturizing factors (NMFs) and corneocyte surface topography were suggested as biomarkers for irritant dermatitis.ObjectivesTo investigate how exposure to different irritants influences corneocyte surface topography, NMF levels and the barrier function of human skin in vivo.MethodsEight healthy adult volunteers were exposed to aqueous solutions of 60% n‐propanol, 0.5% sodium lauryl sulfate (SLS), 0.15% sodium hydroxide, and 2.0% acetic acid, and distilled water, in a repeated irrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 36 publications
6
44
0
Order By: Relevance
“…The changes in the barrier function parameters after cumulative exposure to 60% n ‐propanol in a TRIT in healthy volunteers were initially studied by Kappes et al Using the same exposure model, we recently showed significant impairment of the permeability barrier function along with alterations of the corneocyte surface topography after exposure to the same concentration of the irritant and pointed to previously underestimated or unknown aspects of the irritant potential of short‐chain alcohols . Furthermore, the findings of the present and our previous studies are in agreement with observations of an earlier om‐TRIT study on the effects of 60% n ‐propanol and 0.5% SLS in the human skin in vivo as well as with the results of a recent controlled application test by Cartner et al, showing significant barrier function impairment after exposure to 70% n ‐propanol in healthy female volunteers .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The changes in the barrier function parameters after cumulative exposure to 60% n ‐propanol in a TRIT in healthy volunteers were initially studied by Kappes et al Using the same exposure model, we recently showed significant impairment of the permeability barrier function along with alterations of the corneocyte surface topography after exposure to the same concentration of the irritant and pointed to previously underestimated or unknown aspects of the irritant potential of short‐chain alcohols . Furthermore, the findings of the present and our previous studies are in agreement with observations of an earlier om‐TRIT study on the effects of 60% n ‐propanol and 0.5% SLS in the human skin in vivo as well as with the results of a recent controlled application test by Cartner et al, showing significant barrier function impairment after exposure to 70% n ‐propanol in healthy female volunteers .…”
Section: Discussionsupporting
confidence: 92%
“…Compared with alkaline soaps and detergents, short‐chain alcohols are considered to have a relatively low skin irritation potential . However, in two recent studies, we found considerable and previously unknown negative effects of 60% n ‐propanol on the permeability barrier function and corneocyte surface topography in the healthy human skin in vivo . Therefore, in the present study, we aimed to extend our previous findings by investigating the effects of the applied irritant concentration and the relative contribution of workplace‐relevant co‐exposures in healthy volunteers and individuals with atopic dermatitis (AD), known to have an increased risk for irritant HE.…”
Section: Introductionmentioning
confidence: 89%
“…A recent study showed that anionic surfactants affect the barrier integrity through disruption of tight junctions . The changes on molecular level observed after exposures to SLS are consistent with reduction in the skin barrier function commonly assessed as transepidermal water loss (TEWL) and decreased hydration …”
Section: The Effects Of Skin Irritants and Allergens On The Skin Barriermentioning
confidence: 64%
“…Although hand sanitizers seem to be less damaging for the skin barrier than soaps it has been demonstrated that they have the ability to induce changes in the SC; for example, n‐propanol has pronounced denaturing effects on the SC proteins, profilaggrin processing, and desquamatory SC enzymes . Consistently, Soltanipoor et al showed that n‐propanol caused remarkable changes in corneocyte surface topography and that this effect was strongly associated with a decrease in NMF and SC hydration. In the same study of Soltanipoor et al the changes in corneocyte surface topography were also observed after exposure to SLS and NaOH, but not after acetic acid, likely due to its low irritant potency.…”
Section: The Effects Of Skin Irritants and Allergens On The Skin Barriermentioning
confidence: 94%
“…This view would be supported by the close (anti)correlation to NMF: The more NMF, the better are the working conditions for proteases, which degrade the corneodesmosomes (ie, lower DTI). At the lower end of complexity, it could be excluded that the link between DTI and skin hydration (assessed via capacitance) can simply be mimicked by drenching the tape strips in water or by occluding skin areas with tape …”
Section: Ex Vivo Methods For Barrier Assessmentmentioning
confidence: 99%